Budi daya cacing sutra (Tubifex sp.) dengan sistim air mengalir di Balai Perikanan Budidaya Air Tawar Tatelu (BPBAT), Propinsi Sulawesi Utara - Ngatung, Jefrikardus E. E.; Pangkey, Henneke; Mokolensang, Jeffrie F. (e-Journal BUDIDAYA PERAIRAN, 2017)
The field work training of silk worm culture was done in one month at Balai Perikanan Budidaya Air Tawar Tatelu (BPBAT), Province of North Sulawesi, from May to June, 2016.  The media used are poultry dung (chicken manure) and EM4 with a flowing water system and fed with additional tofu waste.  The initial spread of silk worm seeds was 75 g / m2, and the results obtained were silk worm biomass of 150 g / m2, with the measurement of water quality parameters for DO, temperature and pH are respectively 1.61 ppm, 24.4-27.7° C and 6.1-7.3.Keywords:  aquaculture, life feed, silk worm, Tubifex sp., water quality